HiPLA: High-throughput imaging Proximity Ligation Assay - Serebryannyy, Leonid A. (Methods, 2018)
Protein-protein interactions are essential for cellular structure and function. To delineate how the intricate assembly of protein interactions contribute to cellular processes in health and disease, new methodologies that are both highly sensitive and can be applied at large scale are needed. Here, we develop HiPLA (high-throughput imaging proximity ligation assay), a method that employs the antibody-based proximity ligation assay in a high-throughput imaging screening format as a novel means to systematically visualize changes to protein interactomes. Using HiPLA with a library of antibodies, we probe the interaction of 60 proteins and associated post-translational modifications (PTMs) with the nuclear lamina in a model of the premature aging disorder Hutchinson-Gilford progeria syndrome (HGPS). We identify a subset of proteins that differentially interact with the nuclear lamina in HGPS. In combination with quantitative indirect immunofluorescence, we find that the majority of differential interactions were accompanied by corresponding changes in expression of the interacting protein. Taken together, HiPLA offers a novel approach to probe cellular protein-protein interaction at a large scale and reveals mechanistic insights into the assembly of protein complexes.